Ancient beer production : a thesis presented in partial fulfillment of the requirements for the degree of Masters in Food Technology, Massey University, Auckland, New Zealand - Sathyanarayanan, Barath Kumar (Massey University, 2022)
Background: Beer is considered to be one of the major historical achievements of mankind over the past several centuries in the area of fermented beverages. Beer has the ability to unite people under various cultural traditions and has geographically spread out throughout the world. It varies from nation to nation under the basis of its ingredients, production processes, sensory properties etc. However, the exploration of ancient beer research has been increasing only in the past few decades given the availability of modern analytical tools. Various civilisations adapted the concept of beer into their own cultures in a unique aspect as a safe-to-drink beverage, as opposed to drinking untreated water. Based on an archaeology study of a 5000-year-old beer recipe, one such civilisation named Yangshao (in Shaanxi, Northern China) was considered for this project. Objective: To recreate the ancient beer recipe that has been obtained from the above-mentioned Shaanxi district and adopt its ingredients into contemporary beer brewing methods. In this project, the physicochemical properties were analyzed and a focus group was conducted to understand consumer opinions and attitudes about the sensory characteristics of this beer. Methods: Initially, the ancient ingredients were identified and prepared to suit the modern brewing process. Processes such as milling, mashing, fermentation, conditioning were fine-tuned in order to suit them for the ancient beer reproduction. Physicochemical properties such as brix, colour, pH, specific gravity, alcohol content etc. using methods such as spectrophotometry, gas chromatography, refractometry etc., were investigated. A focus group was used collect qualitative information on the opinions of modern-day consumers on the ancient beer samples. Results: The beer was recreated by identifying the ingredients and their proportions, adjusting various production process parameters such as milling (15mm roller gap for barley & 10mm roller gap for adjuncts), mashing (double temperature mashing with 60 minutes), fermentation (primary and secondary fermentation), conditioning (at 4℃ for 1 week) etc. Recreated beer had similar physicochemical properties to certain commercial beers such as ales, lagers, Weiss beers etc. The similarities identified included alcohol content to modern-day beers (4.1% ABV), similar pH as ales (4.2) however focus group discussions revealed some uniqueness of this beer compared to modern beers. The unique factors included its pale colour, lack of bitterness, and increased sourness in its taste to its high malty aroma. Conclusion: The optimisations made on the physical processes resulted in a mash which yielded maximum amount of sugar extraction from the grains and a well carbonated final beer. The physicochemical analysis revealed that certain attributes of the ancient beer like pH, alcohol content were similar to some modern-day beers but overall the final beer product was unique and contrasting. The recreated ancient beer was well received by the focus group participants and most of them indicated their preference for the sample that incorporated hops. Also, the results proved that an additional carbonation process can be recommended in order to enhance the fizziness of the beer. Overall, the ancient beer proved to be feasible in modern-day brew society considering certain changes in ingredients (hops) and production processes (carbonation, filtration) are implemented in future.
Keywords: 300601 Beverage chemistry and beverage sensory science